AND OTHER FACTORS OF THE ARCHITECTURAL ENVIRONMENT OF CROSS-BORDER AREA - and (Municipal economy of cities (Technical science), 2013)
The factors forming the architectural environment of cross-border areas. The positive aspects of the formation of the territory’s infrastructure.